2016
DOI: 10.5194/gmd-2016-207
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Global Gridded Crop Model evaluation: benchmarking, skills, deficiencies and implications

Abstract: Abstract. Crop models are increasingly used to simulate crop yields at the global scale, but there so far is no general framework on how to assess model performance. We here evaluate the simulation results of 14 global gridded crop modeling groups that have contributed historic crop yield simulations for maize, wheat, rice and soybean to the Global Gridded Crop Model Intercomparison (GGCMI) of the Agricultural Model Intercomparison and Improvement Project (AgMIP). Simulation results are compared to reference d… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
81
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 53 publications
(83 citation statements)
references
References 17 publications
2
81
0
Order By: Relevance
“…Overall, Supplementary Fig. 4, but also the broader benchmarking evaluation in the context of Global Gridded Crop Model Intercomparison (GGCMI)6376 provide evidence for LPJmL's capability of representing most relevant mechanisms of climate-induced signals in observed yields, in particular those linked to water stress. This is key to explaining inter-annual yield variability and eventually feedbacks from water management on food production levels.…”
Section: Methodsmentioning
confidence: 77%
See 1 more Smart Citation
“…Overall, Supplementary Fig. 4, but also the broader benchmarking evaluation in the context of Global Gridded Crop Model Intercomparison (GGCMI)6376 provide evidence for LPJmL's capability of representing most relevant mechanisms of climate-induced signals in observed yields, in particular those linked to water stress. This is key to explaining inter-annual yield variability and eventually feedbacks from water management on food production levels.…”
Section: Methodsmentioning
confidence: 77%
“…The LPJmL model has been validated extensively in terms of biogeochemical, ecological and hydrological processes for both natural and agricultural systems5960616263. It has the unique feature to simulate vegetation dynamics and the carbon and water cycle in a single consistent framework and therefore bridges categories between a global gridded crop model and a global hydrological model64.…”
Section: Methodsmentioning
confidence: 99%
“…The simulation data of 12 global gridded crop models that participated in the Global Gridded Crop Model Intercomparison of the AgMIP were obtained from http://www.rdcep.org/research-projects/ggcmi (Müller et al, ) (hereafter the AgMIP global crop models). We used the historical simulations for maize without irrigation from 1981 to 2010, at 0.5° spatial resolution.…”
Section: Methodsmentioning
confidence: 99%
“…Most modeling efforts, for example, the participant models in the Agricultural Model Inter‐comparison and Improvement Project (AgMIP), focus on the temperature response and CO 2 effects on crop yield (Bassu et al, ; Deryng et al, ; Maiorano et al, ; Schauberger et al, ; Wang et al, ), whereas the precipitation response and the excessive rainfall impact have for some time not been in the focus (Lobell & Asseng, ; Rosenzweig, Tubiello, Goldberg, Mills, & Bloomfield, ; van der Velde, Tubiello, Vrieling, & Bouraoui, ). The extent that excessive rainfall adversely affects maize production in the United States is still largely unknown, especially when compared with the impact of drought (i.e., deficient rainfall), and how well current process‐based global gridded crop models (i.e., global crop models participated in the AgMIP, as opposed to point‐based models; Müller et al, ) simulate such impacts has not been evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Statistical crop models usually express the relationship between yield or yield components and weather parameters in a form of regression equations (e.g., Lobell & Burke, ), which are calibrated by using corresponding observed yield and weather data varying in time or space or in both domains. Process‐based crop models simulate the key processes of the soil–plant system, including crop development (phenology), biomass accumulation, yield, water, and nutrient uptake, while taking into account the effects of environmental stresses as well as plant responses to elevated atmospheric carbon dioxide concentrations (e.g., Müller et al, ). Fodor et al () reported that the vast majority of soybean‐related climate change impact studies using land suitability and/or crop models project positive changes for Sub‐Saharan Africa.…”
Section: Models As Tools For Predicting Climate Change Impacts On Agrmentioning
confidence: 99%